THE EFFECT OF JOB ATTACHMENT AND INCOME SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. LAMBANG BUMI PERKASA - Suhariyanto Suhariyanto; Bovie kawulusan; David Ariswandy (University of Sang Bumi Ruwa Jurai, 2023)
Companies that have resources such as assets, machines, and methods cannot provide optimal results if they are not supported by human resources who have more optimal performance in the face of high competition. This study aims to examine the effect partially or simultaneously of variables of job attachment and income satisfaction on employee performance at PT. Lambang Bumi Perkasa. This study took 40 respondents as a sample and used sampling using simple random sampling techniques. The analytical tool used in this study is multiple linear regression. The tests carried out are with classical assumption tests, F tests, and t tests. The results of this study explain that: Work engagement has an influence on Employee Performance at PT. Lambang Bumi Perkasa in Terbanggi Ilir Central Lampung. The Job Attachment has an influence of 34 percent on the Performance of PT. Lambang Bumi Perkasa. Income Satisfaction has an influence on Employee Performance at PT. Lambang Bumi Perkasa in Terbanggi Ilir Lampug Tengah, while Income Satisfaction has an influence of 54.6 percnet on the Performance of PT. Lambang Bumi Perkasa. Work Attachment and Income Satisfaction together have an influence on Employee Performance at PT. Lambang Bumi Perkasa in Terbanggi Ilir Central Lampung.